Influence of the organic cation disorder on photoconductivity in ethylenediammonium lead iodide, NH3CH2CH2NH3PbI4. Issue 25 (6th June 2018) - Glushkova, Anastasiia; Arakcheeva, Alla; Pattison, Philip; Kollár, Márton; Andričević, Pavao; Náfrádi, Bálint; Forró, László; Horváth, Endre
Abstract : We report the synthesis, crystal structure, and photoconductivity of EDPbI4 . The ED disorder depends on the thermal treatment of EDPbI4 . The increased disorder is associated with increased photoconductivity. Abstract : We report the synthesis and crystal structure of an organic–inorganic compound, ethylenediammonium lead iodide, NH3 CH2 CH2 NH3 PbI4 . Synchrotron-based single crystal X-ray diffraction experiments revealed that the pristine and thermally treated crystals differ in the organic cation behaviour, which is characterized by a partial disorder in the thermally treated crystal. Based on current–voltage measurements, increased disorder of the organic cation is associated with enhanced photoconductivity. This compound could be a potential candidate for interface engineering in lead halide perovskite-based optoelectronic devices.